Praktek Jual Beli Barang Sistem Arisan di Desa Gardusayang Kecamatan Cisalak Kabupaten Subang Dalam Perspektif Ekonomi Syariah - Rina Fitriani; Jalaludin Jalaludin; Ahmad Damiri (EKSISBANK (Ekonomi Syariah dan Bisnis Perbankan), 2021)
This research was conducted in Gardusayang Village, Cisalak District, Subang Regency. bermuamalah is one form of convenience for humans to fulfill everything related to their daily needs as living creatures and social beings, among the actions of the community to meet material needs is social gathering, but members still do not understand the practice of buying and selling goods arisan system in Islamic economic perspective. This study aims to provide a description of the implementation of the sale and purchase of social gathering system items, a review of the sharia economy on the sale and purchase of social gathering system goods and the impact of the sale and purchase of social gathering system goods. This research is a qualitative type with an empirical approach, data collection techniques used are observation, interviews, documentation. In this study the data source consisted of primary data and secondary data. From the results of the study that the practice of buying and selling goods arisan system in the Village of Gardusayang Cisalak-Subang in the implementation of the social gathering members have been willing and agreed to accept the social gathering system made by the head of the social gathering that the members are willing to pay the social gathering according to a mutually agreed period of time. In this economic review of arisan sharia, it is permissible in Islamic Shari'a because it brings more benefits to arisan participants as a means of mutual assistance between them, so that it can have an effect or impact on improving family welfare, because through this arisan they can meet various his necessities such as buying something that might be difficult to buy if he only relied on the opinion of his family